Post Covid-19 Tourist Attraction Management Strategy in Kampoeng Bisnis Tegal Waru - Liliana Dewi; Glenn Wibisono; Thoriq Ba'mar; Rosa Adilla; Dimas Adhitya Bastian (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
This study aims to determine the tourism attraction management strategy in Kampoeng Bisnis Tegal Waru after the Covid-19 pandemic in Jl. Pulekan No. 31, RT.01/RW01, Ciampea Bojong Jengkol, Bogor. The research method used in this research is qualitative, where the results obtained in this study are from interviews and observations conducted in Kampoeng Bisnis Tegal Waru. The interviews and observations carried out were on the manager and owner as well as two Micro Small Medium Enterprise (MSME) in Kampoeng Bisnis Tegal Waru. The resulting study of the post-Covid-19 tourist attraction management strategy implemented by the founder and owner of Kampoeng Bisnis Tegal Waru was the assistance in the form of capital funds, providing MSME owners with additional knowledge and skills in the field of Social Entrepreneurship, counseling regarding health protocols and getting the MSMEs ready after the pandemic.